Pengaruh Earning Per Share (EPS) dan Book Value Per Share (BVPS) Terhadap Harga Saham PT Telekomunikasi Indonesia TBK Periode 2012-2021 - Intan Kurniati; Aria Aji Priyanto (Formosa Journal of Sustainable Research, 2022)
This study aims to determine the effect of Earning Per Share and Book Value Per Share on the stock price of PT. Telekomunikasi Indonesia Tbk period 2012-2021. The method used in this research is quantitative research with associative method, the type of data used is secondary data in the form of financial report data of PT. Telekomunikasi Indonesia Tbk period 2012-2021 . The test uses the classical assumption test, multiple linear regression analysis, hypothesis testing, and determination test with SPSS version 20 statistical processing program. Based on the SPSS test results it can be concluded that Earning Per Share partially has a significant effect on stock prices. And Book Value Per Share has a significant effect on stock prices. And simultaneously (together) Earning Per Share and Book Value Per Share have an effect on stock prices